ANALISIS QUALITY OF WORK LIFE PADA GENERASI X DAN Y ALUMNI FAKULTAS EKONOMI DAN MANAJEMEN IPB - Avianti, Dwi Astrid; Kartika, Lindawati (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The quality of Work Life is one of effort that can be implemented by the company to increase job satisfaction and productivity of employees. Nowadays, employees in Indonesia dominated by Generation X and Y. The respondents of this study are alumni of Economic and Management Faculty of IPB. The objectives of this study are to identify the perception of Generation X and Y towards factors of Quality of Work Life and to formulate a strategy to increase Quality of Work Life based on perceptions of Generation X and Y. The source of primary data obtained by questionnaire method and secondary data obtained by study of literature. This research was using descriptive analysis method, Pairwise Comparison Method, and The House Model. The results of this study indicated 56% perception of Generation X towards factors of QWL appropriate with the theory regarding the factors QWL in Generation X and 52% perception of generation Y towards factors of QWL appropriate with the theory regarding the factors QWL in the generation Y. The strategy that becomes priorities to increase Quality of Work Life of Generation X is a safety at work, compensation, and conflict resolution. The strategy that becomes priorities to increase Quality of WorkLife of Generation Y is career development, compensation, and pride to the company. Keywords: quality of worklife, generation X Y